Institutions under stress and people in distress: institution-building and drought in a new settlement scheme in Sri Lanka - Merrey, Douglas J.; Somaratne, Pallewatte G. (International Irrigation Management Institute, 1989)
This paper analyzes irrigation operational problems, and their institutional causes, on a new irrigation system in southern Sri Lanka, based on research during disastrous drought. The authors offer a number of suggestions for improving the management of this system.